THE EFFECT OF LEG EXTENTION TRAINING ON THE LEG MUSCLE STRENGTH OF FOOTBALL PLAYERS AT SMA NEGERI 3 BANJARBARU - Rachman, Aryadi; Ridha, Sahbana; Saputra, Deny Bagus; Erfandy, Wahyu (Riyadhoh : Jurnal Pendidikan Olahraga, 2024)
Leg muscle strength is an essential component in supporting the performance of soccer athletes, particularly in terms of speed and kicking power. Leg extension exercises are a form of resistance training focused on strengthening the quadriceps (front thigh muscles) by lifting weights with the legs while seated on a leg extension machine. The aim of this study is: to determine whether there is the effect of exercise on the leg extension leg muscle strength of soccer player SMAN 3 Banjarbaru. This research uses quantitative methods of pre-experimental. The study design used pretest and posttest in One Group. The population in this study is a soccer player of SMA 3 Banjarbaru of 20 people, then a sample total sampling technique or sample is saturated. The survey results revealed that leg extension exercise influences leg muscle strength in soccer players SMAN 3 Banjarbaru in accordance with the criteria of testing the value of Sig. (2-tailed) 0.000 <0.05. Leg extension exercise resulted in an increase in leg muscle strength in soccer players SMAN 3 Banjarbaru amounted to 15 440.